2020
DOI: 10.1021/acsomega.0c01732
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Performance of Carboxylate-Alumoxane Nanoparticles as a Novel Chemically Functionalized Inhibitor on Asphaltene Precipitation

Abstract: In recent years, researchers have attempted to find some practical approaches for asphaltene adsorption and the prevention or postponement of asphaltene precipitation. Among different techniques, nanotechnology has attracted the researchers' attention to overcome the formation damage resulting from the deposition of asphaltenes. In this study, the application of two types of carboxylate-alumoxane nanoparticles (functionalized boehmite by methoxyacetic acid (BMA) and functionalized pseudo-boehmite by methoxyace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Also, the images c and d clearly show the mesoporousness of the surface of the structure. Therefore, by observing the change in the morphology of the raw components used in the adsorbent structure compared to the final structure, along with other analyzes provided to confirm the prepared structure, it confirms the success of the adsorbent preparation [ [89] , [90] , [91] ].
Fig.
…”
Section: Characterization Of Cs@tdi@edta@γ-alo(oh)mentioning
confidence: 71%
“…Also, the images c and d clearly show the mesoporousness of the surface of the structure. Therefore, by observing the change in the morphology of the raw components used in the adsorbent structure compared to the final structure, along with other analyzes provided to confirm the prepared structure, it confirms the success of the adsorbent preparation [ [89] , [90] , [91] ].
Fig.
…”
Section: Characterization Of Cs@tdi@edta@γ-alo(oh)mentioning
confidence: 71%
“…Although most of the recent research focused on a single nanoparticle, polymer-functionalized metal oxide nanoparticles have attracted more and more attention in recent years. Researchers synthesized NiO/SAPO-5 [ 92 ], NiO/ZSM-5 [ 93 ], Fe 3 O 4 -polythiophene [ 94 ], carboxylate-aluminoxane [ 95 ], and other composite nanoparticles, and found that they exhibit more excellent performance in inhibiting asphaltene.…”
Section: Asphaltene Nano-inhibitorsmentioning
confidence: 99%
“…Bagherpour et al [ 95 ] prepared two kinds of carboxylate–alumoxane nanoparticles using boehmite and pseudo-boehmite as raw materials. The structure is shown in Figure 8 .…”
Section: Asphaltene Nano-inhibitorsmentioning
confidence: 99%
“…119 MD simulations of asphaltene aggregation and adsorption in heptane and toluene and confined in calcite and silica pores 13 wt % Small nanoparticles showed higher asphaltene adsorption capacity and thus inhibits asphaltene aggregation more effectively than large nanoparticles. Carboxylate-alumoxane 336 10−100 8.1 wt % Nanoparticles with smaller sizes and higher surface areas showed higher asphaltene adsorption capacity. Metal oxides 337 20−160 showed that asphaltene aggregates are smaller in size in confinement compared to in bulk fluids.…”
Section: Aggregation Of Polyaromatic Macromolecules (Eg Asphaltenes) ...mentioning
confidence: 99%